Computers serving plant pathology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Information Technology, Plant Pathology and Biodiversity. Edited by P Bridge, P Jeffries, D R Morse and P R Scott. 1998. 496 pp. ISBN 0 85199 217 X British pounds 49.95 CAB International Wallingford Oxon OX10 8DE UK. Fax: +44 1491 833508 Email: